Ethnobotany of Piperaceae in Nakhon Nayok Province, Central Thailand - PIYAPORN SAENSOUK; THAWATPHONG BOONMA; TAMMANOON JITPROMMA; TRAN VAN CHEN; SURAPON SAENSOUK (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Saensouk P, Boonma T, Jitpromma T, Chen TV, Saensouk S. 2025. Ethnobotany of Piperaceae in Nakhon Nayok Province, Central Thailand. Biodiversitas 26: 2416-2428. This study investigates the ethnobotanical significance of Piperaceae in Nakhon Nayok Province, Central Thailand, documenting the species diversity, traditional uses, and cultural importance of this plant family. A total of 31 Piperaceae taxa were recorded, comprising two genera: Peperomia (22 taxa) and Piper (nine species). Among these, only eight species are native, while 23 taxa are introduced, highlighting the predominance of non-native species in the area. Piper nigrum exhibited the highest Cultural Index (1.11), followed by Piper sarmentosum (0.84), Piper betle (0.66), Peperomia pellucida (0.59), and Piper retrofractum (0.5), with other taxa scoring below 0.5. The most common use category was ornamental plants (Cultural Index: 9.49), followed by vegetables and spices (1.89), herbal medicine (0.94), and cultural practices and rituals (0.51). The whole plant was the most frequently used part, especially for ornamental purposes, while the leaves were the most frequently used for therapeutic purposes. In therapeutic applications, Piperaceae plants are primarily used to treat gastrointestinal issues, followed by respiratory ailments, cutaneous conditions, and musculoskeletal and joint diseases. They also address disorders related to nutrition, blood, the cardiovascular system, and conditions affecting the ear, nose, oropharynx, oral cavity, and the endocrine system, respectively. These findings emphasize the diverse applications of Piperaceae species in local traditions, particularly their ornamental, culinary, and medicinal uses. The study provides valuable insights into the ethnobotanical knowledge of this plant family, emphasizing the importance of conservation efforts in preserving both native species and traditional botanical knowledge amid changing environmental and socio-economic conditions.